Student challenges completing the matrix material story question - Nandang Nandang; Mochammad Taufan; Najwa Noviana (Polyhedron International Journal in Mathematics Education, 2023)
This study aims to determine the difficulties faced by students in solving the matrix material story problem and the factors causing it. This study used a qualitative approach with research subjects in class XI, which consisted of three female students. Determination of research subjects using a purposive sample technique. Data collection techniques in this study used observation, interviews, documentation in the form of pictures and videos, and field notes. The results of this research are the difficulties faced by students in solving the matrix material story problems, namely: the steps for solving problems according to Polya, the material matrix, and the time. Factors that cause students difficulty in solving the matrix material story problems, namely: (1) students are not accustomed to using Polya's steps, (2) not writing stages 1 to 4 of Polya's steps because they are still confused about the placement of the stages, (3) not writing the explanations in the second stage, namely problem-solving planning, (4) not writing the fourth stage, which is checking the results again or verification, (5) students still have not mastered the matrix material because their learning has been using online or online, (6) calculation errors, (7) time in working on story problems with limited matrix material due to nourishing learning during the Covid-19 pandemic.